2020
DOI: 10.4103/jfmpc.jfmpc_381_20
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the services of ASHA workers on antenatal and postnatal care in a district of western Uttar Pradesh, India

Abstract: Context: India accounts for 17% of the population, contributes to about 19% of maternal deaths, and 21% of childhood deaths of the world. Antenatal and postnatal services were one of the most important works done by ASHA workers. Aims: The objective of this study was to assess the services provided by ASHA workers in a district of western Utter Pradesh to her beneficiaries regarding antenatal and postnatal care. Settings and Design: A cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“… 38 However, research in several Indian states found ANC services provided by ASHA workers were not adequate. 39 In our study, women’s literacy and affiliation with SHGs was found to be positively associated with ANC attendance, likely through increased awareness, self-efficacy or perception of ANC as social norm. These findings have likely been influenced by the improvements in public facilities through the facility-based component of the programme over time.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“… 38 However, research in several Indian states found ANC services provided by ASHA workers were not adequate. 39 In our study, women’s literacy and affiliation with SHGs was found to be positively associated with ANC attendance, likely through increased awareness, self-efficacy or perception of ANC as social norm. These findings have likely been influenced by the improvements in public facilities through the facility-based component of the programme over time.…”
Section: Discussionmentioning
confidence: 50%
“…Analyses of Indian Human Development Survey data showed that exposure to ASHA services was associated with a 17% and 5% increase in women attending 1 and 4+ ANC visits, respectively 38. However, research in several Indian states found ANC services provided by ASHA workers were not adequate 39. In our study, women’s literacy and affiliation with SHGs was found to be positively associated with ANC attendance, likely through increased awareness, self-efficacy or perception of ANC as social norm.…”
Section: Discussionmentioning
confidence: 99%